Effectiveness of the implementation of the Pancasila student profile strengthening project on improving the character of students of SMAK 7 Penabur Jakarta - Silalahi, Verry Albert Jekson Mardame; Tarigan, Ervan Periangan; Manurung, Susy Pramanita; Simanungkalit, Ester Venny Augusta; Siringoringo, Yosri Tuty Asni; Kusuma, Brandon Henry; Sianturi, Oktavia Intan; Lumbanraja, Hendro Samauli (MID Publisher International, 2024)
This study examines the effectiveness of the implementation of the Pancasila Student Profile Strengthening Project (P5) in improving the character of students at SMAK 7 PENABUR Jakarta. The Pancasila Student Profile Strengthening Project is designed to integrate Pancasila values—such as belief in God, humanity, unity, democracy, and social justice—into daily student activities. The study aims to measure how effective the project is in shaping student character, identify factors influencing its effectiveness, and analyze student and teacher perceptions of the program. Using a quantitative research method with purposive sampling, data were collected through surveys and interviews. Results show that Pancasila Student Profile Strengthening Project positively impacts students' character development, particularly in areas of cooperation, critical thinking, and social responsibility. However, the study also highlights challenges, including varying levels of student engagement and resource limitations. The findings suggest that continuous evaluation and improvement of the program are necessary to maximize its benefits. The study implies that schools should provide better support for teachers and include more practical applications of Pancasila values in both curricular and extracurricular activities. It is recommended that future research explore long-term impacts and scalability of the Pancasila Student Profile Strengthening Project program across different educational settings. Overall, this study contributes to the theoretical understanding of character education and offers practical insights for improving value-based educational initiatives.